Preparation and characterization of modified polypropylene/palm kernel shell (PP/PKS) biocomposites - Murad Salem Mohamed Omar (School of Material Engineering, 2012)
The primary objective of this work is to characterize and determine the properties of Polypropylene (PP)/palm kernel shell (PKS) biocomposites on a different composition of PKS loading with an aim of developing a new natural filler material as useful filler in thermoplastic based composites.